Literatura de múltiplos destinatários: perspectiva metateórica à luz do leitor real - Duarte, Cristina Rothier (2023)
In contemporaneity, we have recurrently seen narratives which are classified either as literature for multiple recipients, dual audience or crossover fiction, due, according to some specialists (FALCONER, 2009; RAMOS; NAVAS, 2015; BECKETT, 2009), both to the theme, as well as to certain textual characteristics they have. According to Beckett's (2009) understanding, the literary texts upon which this phenomenon occurs present a narrative communication that flows in two directions, and the levels of addressing are determined not only by the addressers, but also by the addressees, so that age boundaries break down. Notwithstanding the importance of the reader's participation in this process of expanding the audience, as initially intended by some legitimizing instances (publishing market, awarding institutions, among others), the reader's particularities within this context of interaction with the literary text had not yet been given attention. The general objective of this research is, therefore, to analyze the way communication takes place between an adult reader and a juvenile literary text, considering, however, fiction by multiple recipients by critics. With regard to specific objectives, we aim at: i. presenting a historical outline of Brazilian children's and youth literature; ii. undertaking theoretical discussions about the (il)legitimacy of youth literature and theoretical approaches to literature for multiple recipients (crossover fiction); iii. contributing metatheoretically to studies that deal with this type of literary text, based on the theoretical articulation proposed by Carmen Santos (2009) in the light of the theory of the aesthetic effect and the historical-cultural theory; iv. verifying the reading process which resulted in the aesthetic effect experienced by an adult person, the researcher, in interaction with the youth literary text Aos 7 e às 40 (2013), by João Anzanello Carrascoza, via Mapping of Aesthetic Experience – MAPEE (SANTOS, C., 2009, SANTOS; COSTA, 2020). The theoretical foundation that supports this thesis consists of studies concerning the theory of the aesthetic effect (ISER, 1996; 1999a) and the historical-cultural theory (VYGOTSKY, 2007; 2008). As to this research methodology it involves the phenomenological method, as it enables the scrutiny of the essence of the reading act of a real reader; the inductive, since, based on the results obtained through the MAPEE, we identify idiosyncrasies of the text and the reader that create an aesthetic effect; and the autoethnographic, an adequate procedure due to the researcher's integral connection with the investigated phenomena and documents. The analysis of the act of reading a crossover text allowed us, as a result, at identifying the particularities both of the reader and of the literary text, which play a conditioning role in the phenomenon of crossing the age limits which is established by the publishing market.